Does Higher Student Confidence Lead to Better Science Literacy? - Janeusse Fratiwi, Nuzulira; Susilowati, Nur Endah; Irwandani, Irwandani (U-Teach: Journal Education of Young Physics Teacher, 2025)
Student confidence plays a crucial role in supporting students’ ability to engage effectively with scientific concepts, yet its impact on science literacy remains underexplored. This study aims to analyze the relationship between student confidence and their science literacy skills in physics. A quantitative correlational design was employed to investigate this association among 50 high school students (aged 15-17 years), consisting of 28 females and 22 males, from one of Public High School in Lampung. Student confidence levels were measured using a structured questionnaire, while science literacy was assessed through a standardized test on the physics topic of Density. Data analysis involved Pearson’s correlation coefficient and significance testing using Fisher’s method. The results demonstrate a strong positive correlation (r = 0.80) between student confidence and science literacy, with statistical significance (t = 12.97, p < 0.05). These findings suggest that higher student confidence is associated with better science literacy, indicating the importance of fostering confidence to enhance science learning outcomes in physics education